Regenerated cellulose scaffolds: Preparation, characterization and toxicological evaluation. (20th January 2016) - de Araújo Júnior, Adalberto M.; Braido, Guilherme; Saska, Sybele; Barud, Hernane S.; Franchi, Leonardo P.; Assunção, Rosana M.N.; Scarel-Caminaga, Raquel M.; Capote, Ticiana S.O.; Messaddeq, Younès; Ribeiro, Sidney J.L.
Abstract: Regenerated cellulose scaffolds (RCS) may be used as alloplastic materials for tissue repair. In this work, the RCS were obtained by viscose process and characterized by scanning electron microscopy (SEM), wide angle X-ray diffraction (WAXD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetry analysis (TG). In vitro enzymatic degradation assay and toxicological assays were also evaluated. The physicochemical characterizations revealed the formation of a porous material with distinct thermal profile and crystallinity compared to pristine cellulose pulp. Enzymatic degradation assay revealed that lysozyme showed a mildest catalytic action when compared to cellulase, Tricoderma reesei ( Tr ) . Nevertheless, both enzymes were efficient for degrading the RCS. RCS did not show cytotoxicity, mutagenic or genotoxic effects. The systematically characterization of this work suggests that RCS presented distinct features that make it a viable material for future studies related to the development of scaffolds for biological applications.